1998
DOI: 10.1029/97wr03469
|View full text |Cite
|
Sign up to set email alerts
|

Interannual, seasonal, and spatial patterns of meltwater and solute fluxes in a seasonal snowpack

Abstract: Abstract. Meltwater discharge and electrical conductivity were measured in eight 1 x 1 m lysimeters, and snow accumulation and electrical conductivity of melted samples were measured in snow pits during four snowmelt seasons at Mammoth Mountain, California. The peak snow-water equivalent ranged from 0.57 to 2.92 m over the four melt seasons. Lysimeter discharges ranged from 20% to 205% of the mean flow; however, mean lysimeter flow was representative of snow ablation observed in snow pits. The electrical condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…In addition, several studies have shown significant wintertime dry deposition of NO − 3 -N, in particular close to highways and urban areas (Cape et al, 2004;Dasch and Cadle, 1986;Kirchner et al, 2005). Therefore, the fact that wet deposition concentrations were very similar to snowpack concentrations could be merely a coincidence and may not allow us to infer dry versus wet deposition of NO Previous studies have observed parallel concentration declines of SO 2− 4 and NO − 3 -N during snowpack melt events due to similar early-season ionic pulses that lead to preferential losses of nutrients and other ions (Bales et al, 1989;Harrington and Bales, 1998;Tranter et al, 1986). In support of such potential losses, Fig.…”
Section: -N In the Rockymentioning
confidence: 99%
“…In addition, several studies have shown significant wintertime dry deposition of NO − 3 -N, in particular close to highways and urban areas (Cape et al, 2004;Dasch and Cadle, 1986;Kirchner et al, 2005). Therefore, the fact that wet deposition concentrations were very similar to snowpack concentrations could be merely a coincidence and may not allow us to infer dry versus wet deposition of NO Previous studies have observed parallel concentration declines of SO 2− 4 and NO − 3 -N during snowpack melt events due to similar early-season ionic pulses that lead to preferential losses of nutrients and other ions (Bales et al, 1989;Harrington and Bales, 1998;Tranter et al, 1986). In support of such potential losses, Fig.…”
Section: -N In the Rockymentioning
confidence: 99%
“…It is well known from work in temperate latitudes that the early pulse of water from initial snow melt typically includes an 'ionic' pulse of major elements [72][73][74][75] and dissolved and particulate Hg. [76] In Amituk Lake in the Canadian High Arctic, snowmelt delivered the most THg during spring in June and early July [22,77] but 59 % of the THg delivered to Amituk Lake during the snowmelt period was directly discharged through lake outflow because of the limited mixing between surface and underlying water.…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
“…The relative saturation in the vadose zone controls the stream connectivity and release of water and nutrients from subsurface storage into stream systems (McNamara et al, 2005; M. W. . Soil moisture during this time is driven by snowmelt that can impact the water availability for plant production (Molotch et al, 2009;Harpold et al, 2015) as well as the ionic signature of soil moisture and stream flow (Harrington and Bales, 1998). For these reasons the connections between snowmelt and soil moisture are critical in understanding the hydrologic cycle in snow-dominated headwater systems (Jencso et al, 2009), particularly in the face of a changing climate that will alter the snowmelt season and resulting hydrological dynamics (Adam et al, 2009;Clow, 2010;Clilverd et al, 2011;Harpold et al, 2012;Rasmussen et al, 2014;Fassnacht et al, 2016).…”
Section: Introductionmentioning
confidence: 99%